Male fertility: summary overview of the publications October – December 2021 - D. S. Rogozin (Вестник урологии)
The article presents an overview of the most significant publications on the topic of male infertility. The main selection criteria were the practical significance of the article, as well as the impact factor of the journal in which it was published, according to the SCImago Journal Rank. As a result, a list of 10 articles published in the IV quarter (October — December) of 2021 was compiled. The review includes articles on the following topics: genetic causes of male infertility, the effectiveness of antioxidants, the use of testicular spermatozoa in Intra Cytoplasmic Sperm Injection, the impact of DNA fragmentation of spermatozoa on the results of assisted reproductive technology, the relationship of male fertility with physical activity, the consumption of sweetened beverages and vitamin D intake, as well as the prognostic value of blood anti-Mullerian hormone levels before testicular biopsy.